The Impact of Financial Capital on Contemporary China and Global Development Trends - Zhang, Jiaxin (International Journal of Global Economics and Management, 2024)
Since the 1980s, financial capital has gradually assumed a dominant role in global economic development. Emerging as a new form of capital, financial capital has expanded globally; however, its essence remains tied to the general laws of economic development. The historical trajectory of financial capital has been profoundly shaped by the unbalanced political economy led by capitalist states, cyclical global financial crises, and the transformation of Western capitalist values, which has led people to pursue the "greed" inherent in capital. Marx analyzed the development of capitalism and posited that capitalist crises are inevitable, with the unlimited expansion of capital being a fundamental characteristic of capitalist development. Therefore, in critiquing the globalization of financial capitalism, it is necessary to base the analysis on Marx’s theoretical framework regarding the logic of capital, while also focusing on the developmental trends of capital on the global stage. Furthermore, the implications of this development require careful analysis and consideration. In this context, China’s unwavering commitment to the path of socialism with Chinese characteristics should also be thoroughly examined, with a view to building a community of shared future for humanity.